THE ROLE OF MODERN INFORMATION TECHNOLOGIES IN MOTHER LANGUAGE AND LITERATURE EDUCATION (Conferencea, 2023)
Language plays a fundamental role in human communication and the preservation of culture. Through language, we express our thoughts, emotions, and ideas. It is the medium through which literature is created and passed down from generation to generation. Therefore, it is crucial to provide quality education in mother language and literature to ensure its preservation. In today's digital age, modern information technologies have revolutionized the way we teach and learn. These technologies have significantly contributed to enhancing education in mother languages and literature.